2007
DOI: 10.1111/j.1439-0531.2007.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Morphology in the Domestic Cat, and its Relation with Fertility: A Retrospective Study

Abstract: Knowledge about normal ranges in semen quality and the association between sperm morphology and fertility in felids is limited. The aims of this retrospective study were to (1) define a normal spermiogram in cats; (2) evaluate possible effects of season, age and breed on sperm morphology; and (3) evaluate the relationship between sperm morphology and fertility. Semen samples collected by electroejaculation from 52 cats were evaluated for sperm morphology. The cats constituted two groups: a general population o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
49
2

Year Published

2011
2011
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 30 publications
12
49
2
Order By: Relevance
“…To the best of our knowledge, the current study is the first to compare quality parameters of fresh sperm obtained by three different methods of sperm collection from the same male cats-urethral catheterization after medetomidine administration, electroejaculation and epididymal slicing after orchiectomy. The results obtained in our study confirm that good-quality ejaculates can be collected by EE and EP (Axnér & Linde-Forsberg, 2007;Filliers et al, 2010;Johnston et al, 2001;Lengwinat & Blottner, 1994;Zambelli & Marco, 2006). The evaluation of quality parameters of sperm from these two methods indicated similar results.…”
Section: Discussionsupporting
confidence: 87%
“…To the best of our knowledge, the current study is the first to compare quality parameters of fresh sperm obtained by three different methods of sperm collection from the same male cats-urethral catheterization after medetomidine administration, electroejaculation and epididymal slicing after orchiectomy. The results obtained in our study confirm that good-quality ejaculates can be collected by EE and EP (Axnér & Linde-Forsberg, 2007;Filliers et al, 2010;Johnston et al, 2001;Lengwinat & Blottner, 1994;Zambelli & Marco, 2006). The evaluation of quality parameters of sperm from these two methods indicated similar results.…”
Section: Discussionsupporting
confidence: 87%
“…Although this combination has proven to be efficient, objective and useful for the evaluation of sperm subpopulations in several species, there are no reports that describe the subpopulational characteristics of feline sperm as determined by a CASA-Morph system. Our hypothesis was that teratozoospermia is reflected in different stages of sperm maturation in the epididymal duct and would produce alterations in the sperm morphometric subpopulations that would explain the reduced fertility potential 26. In general, our results indicated that spermatozoa from different epididymal regions such as R1 or R2 could be used as predictors of teratozoospermia in domestic cats because of the morphometric differences reported in the present study between N and T groups.…”
Section: Discussionsupporting
confidence: 53%
“…Our data demonstrated significant differences in sperm morphometric values in different epididymal regions and between donor groups. Marked differences have been found in sperm morphometric subpopulations among epididymal regions and N and T donor groups, and this fact might be associated with fertility, since an unequivocal influence of sperm morphology on feline sperm fertilizing potential has been demonstrated 26. To our knowledge, this is the first research that has documented relevant findings related to testicular morphometry and sperm subpopulations differences during sperm migration through the epididymal duct in both normozoospermic and teratozoospermic domestic cats.…”
Section: Discussionmentioning
confidence: 70%
“…The frequency of all sperm defects was generally low. Comparing the data with domestic carnivores, the majority of the mink would probably have been fertile, although three mink had sperm defects that might impair fertility to some extent (Axnér and Linde Forsberg 2007); one with 40% loose heads, one with 18% pathological heads and one with 20% mid-piece defects. One mink was sterile as it had sperm which all lacked tail.…”
Section: Discussionmentioning
confidence: 93%